Men’s mental health: Connection to urologic health - Matthew, Andrew; Elterman, Dean (Canadian Urological Association Journal, 2014)
Historically, the specialty of urology has focussed on single-system diseases. In recent years, however, there has been increasing recognition of the interconnectivity between the various systems, such as cardiovascular disease, metabolic syndrome, erectile dysfunction, and prostate cancer. This constellation of disease/syndrome and dysfunction may place urologists at the centre of men’s overall health concerns. As urologists consider taking on a leadership role in men’s health, they should also consider their potential in helping men suffering from the significant burden of mental health disorder. Urologists may have a unique opportunity to identify mental health issues in their male patients, influence healthy behaviour change, and successfully refer men, who might otherwise not seek help, to appropriate medical/psychological care.